DAMPAK POC TANDAN KELAPA TERHADAP PRODUKSI DAN PERTUMBUHAN KEDELAI (Glycine Max L.) DI MEDIA GAMBUT - Riono, Yoyon; Yusuf, Elfi Yenny; Rosmida, Rosmida (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
When compared to other varieties of legumes, soybean (Glycine max) L. has the highest vegetable protein content. This study was conducted in Tempuling Village, Tempuling District, Indragiri Hilir Regency, with the goal of determining how POC Coconut Bunches affected soybean plant growth and production. between August and October 2021. POC Coconut Bunches (TK) are given using a Non-Factorial Randomized Group Design (RBD) with seven treatment factors: K3 (30 ml/l), TK4 (40 ml/l), TK5 (50 ml/l), and TK6 (60 ml/l) comprise the control group. As a result, seven treatment combinations with three replications were created, giving rise to 21 experimental units/plots with a total of 63 plants in each plot. The findings demonstrated that the POC Coconut Bunches (TK) treatment had a significant impact on the plant height of 119.89 centimeters, pod weight of 109.00 grams, dry seed weight of 62.14 grams, and 100 seed weight of 24.50 grams, with the best treatment being TK5 (50 milliliters per liter). Keywords: Soybean, POC Coconut Bunches, Peat.